Effect of Surfactant in Formation of Hydroxyapatite Nano-RodsunderHydrothermal Conditions: Hydroxyapatite nano-rods formation - Mehrnaz Salarian,; Ziarat Ali Nemati,; Mehran Solati-Hashjin,; Azadeh Goudarzi,; Seyedeh Sara Shafiei,; Reza Salarian, (Iranian Journal of Pharmaceutical Sciences, 2008)
Hydroxyapatite (HA) nano-rods with uniform morphology and controllable size have been successfully synthesized in the presence of cationic and non-ionic surfactants by a hydrothermal method. (NH4)2HPO4and Ca(NO3)2.4H2O were used as the phosphorus and calcium sources, respectively. The composition of synthesized powders was characterized using X-ray diffraction, and Fourier transform infrared spectrometer and morphology of the resulting powders were examined by scanning electron microscopy. Results revealed the as-prepared HAnano-rods have a typical diameter of about 60-80 nm and an average aspect ratio of about 10-12, which indicates that the mixture of cationic and non-ionic surfactants acts as a soft template to regulate the nucleation and crystal growth of HA. Also effect of hydrothermal temperature was studied on the system.